Dialogical positions in a Whatsapp group regarding the use of chloroquine and hydroxychloroquine in the treatment of Covid-19 (Research, Society and Development, 2021)
The objective of this article is to analyze the established discourses in conversations among members of WhatsApp group “Academia Saudável” (Healthy Academy), having as central issue the controversy of the use of chloroquine and hydroxychloroquine medicines in the treatment of Covid-19. For the analysis, the concepts of concrete utterance, responsible act, alien and authorial discourse, field of communication and discourse genres of Bakhtin's Dialogical Theory of Language and the Circle were summoned. The results demonstrate that each individual of the group has a prominent role in guaranteeing the conversation theme through his/her discursive positionings favorable or not to the use of these drugs in the fight against the new coronavirus.